SIL Verification of Safety Instrumented System for Block Valve System in Gas Pipeline by Using Markov Model Methodology - Kongtong, P.; Chitwong, S. (My University, 2017)
This paper presents about methods for evaluation of safety integrity level (SIL) which is significant to reduce risk of failure of block valve in gas pipeline system by using Markov Model method which refer to International standard IEC 61508/61511. The reason of using Markov Model method is that it takes less time and more flexible than other methods to determine SIL. This method uses a qualitative approach showing Average Probability of Failure (PFDavg) rate data and repairing time from model to implement in further process.
Keywords: Biomimetic; Degrees-of-freedom Safety Instrumented Systems; Markov Models; Probability of Failure on Demand; Redundancy; Safety Instrumented Functions; Safety Integrity Levels; Tracking